Penguatan Literasi Pengasuhan Digital melalui Psikoedukasi pada Kelompok Ibu Bina Keluarga Balita (BKB) Pedukuhan GB Kabupaten Bantul - Regina Tualage; Moordiningsih (HOSPITALITAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
The increasing exposure of toddlers to digital devices has emerged as a developmental concern, particularly as caregivers frequently rely on gadgets for behavioral regulation and daily management. Assessments in Pedukuhan GB indicated limited digital parenting literacy among mothers, especially regarding recommended screen time limits, digital exposure risks, and appropriate parental mediation strategies. This program aimed to enhance knowledge, awareness, and behavioral readiness among mothers of toddlers through a structured psychoeducational intervention. The methods included observation, interviews, focus group discussions, and group-based psychoeducation focusing on digital parenting concepts, screen time guidelines, positive communication, and alternative non-digital strategies reinforced through role play. The results demonstrated a significant improvement in knowledge, evidenced by an increase in mean scores from 72.2% to 93.3%. Qualitative findings further indicated shifts in attitudes and behavioral intentions, including heightened awareness of excessive gadget use risks and greater readiness to implement responsive caregiving strategies. The program also strengthened the capacity of local BKB cadres to ensure continuity of digital parenting education. Psychoeducational intervention proved effective in enhancing maternal competencies in digital parenting and supporting early behavioral change within the family context.